Anterior Temporal Lobe Morphometry Predicts Categorization Ability - Garcin, Béatrice; Urbanski, Marika; Thiebaut de Schotten, Michel; Levy, Richard; Volle, Emmanuelle (Frontiers in Human Neuroscience, 2018)
Categorization is the mental operation by which the brain classifies objects and events. It is classically assessed using semantic and non-semantic matching or sorting tasks. These tasks show a high variability in performance across healthy controls and the cerebral bases supporting this variability remain unknown. In this study we performed a voxel-based morphometry study to explore the relationships between semantic and shape categorization tasks and brain morphometric differences in 50 controls. We found significant correlation between categorization processing speed and the volume of the grey matter in the right anterior middle and inferior temporal gyri. Semantic categorization tasks were associated with more rostral temporal regions than shape categorization tasks. A significant relationship was also shown between white matter volume in the right temporal lobe and performance in the semantic tasks. Tractography revealed that this white matter region involved several projection and association fibers, including the arcuate fasciculus, inferior fronto-occipital fasciculus, uncinate fasciculus, and inferior longitudinal fasciculus. These results suggest that the anterior portion of the right temporal lobe and its interaction with other areas plays a crucial role in categorization processing speed.